Analysis of the Short Story Ibnu Hara by Naguib Mahfouz: A Study in the Sociology of Literature - Ubaidillah, Ahmad Maula; Yavilmun'im, Yavilmun'im (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
The aim of this research is to identify the social phenomena in the short story Ibnu Hara by Najib Mahfuz based on the perspective of literary sociology. Najib Mahfuz is one of the most prominent modern Egyptian writers who was awarded the Nobel Prize in Literature in 1988. Ibnu Hara is one of several short stories included in the anthology Hamasa An-Nujum, which was published a few years after Mahfuz's death. Mahfuz’s short stories often revolve around life in al-hara—the traditional neighborhood—which is depicted as religious yet still deeply rooted in ancient traditions and mystical beliefs. This study uses a qualitative-descriptive method with a literature review approach. From this research, it can be concluded that Ibnu Hara reflects the social, cultural, and religious conditions of Egyptian society during Najib Mahfuz’s lifetime.